Early Renal Involvement in a Girl with Classic Fabry Disease - Fernando Perretta; Norberto Antongiovanni; Sebastián Jaurretche (Case Reports in Nephrology)
Fabry disease is an X-linked lysosomal storage disorder resulting from the deficiency or absence of the enzyme alpha galactosidase A; this defect leads to the systemic accumulation of globotriaosylceramide and its metabolites. Organic involvement in men is well known, but in women it is controversial, mainly due to the random X-chromosome inactivation in each of their cells (Lyon hypothesis). This would explain why women (heterozygotes) present a wide variability in the severity of their phenotype. The manifestations are multisystemic and begin in early childhood, reaching a severe compromise in adulthood. Typical acroparesthesia in hands and feet, gastrointestinal symptoms, angiokeratomas, dyshidrosis, hearing loss, arrhythmias, hypertrophic cardiomyopathy, cerebrovascular accidents, and renal failure can be observed. Nephropathy is one of the major complications of Fabry disease. Glomerular and vascular changes are present before progression to overt proteinuria and decreased glomerular filtration rate, even in pediatric patients. A case of incipient renal involvement in a girl with classic Fabry disease is reported.